2012
DOI: 10.1089/acm.2011.0104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Finding on the Electromagnetic Information Transfer of Specific Molecular Signals Mediated Through the Aqueous System on Two Human Cellular Models

Abstract: These experimental results provide some evidence that water could be tuned in a resonant manner by the EMIT procedure appropriately carried through a carrier frequency provided by the oscillator in a manner that seems related to the chemical structure of the source molecule as, in this case, retinoic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
6
11
0
Order By: Relevance
“…The results of the present study agreed with others suggesting that signals could be transferred to target cells or aqueous systems by an oscillator (BRT instrument) when coupled to two electromagnetic coils, demonstrating the same biological activity, thus mimicking the biological function of the original chemical active molecule [33]. Furthermore, we have previously observed E. histolytica and T. vaginalis trophozoites growth inhibition after treatment with metronidazole electro-transferred water samples, using a BRT device with identical characteristics and conditions of the apparatus used in the present study [31].…”
Section: Results and Conclusionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present study agreed with others suggesting that signals could be transferred to target cells or aqueous systems by an oscillator (BRT instrument) when coupled to two electromagnetic coils, demonstrating the same biological activity, thus mimicking the biological function of the original chemical active molecule [33]. Furthermore, we have previously observed E. histolytica and T. vaginalis trophozoites growth inhibition after treatment with metronidazole electro-transferred water samples, using a BRT device with identical characteristics and conditions of the apparatus used in the present study [31].…”
Section: Results and Conclusionsupporting
confidence: 91%
“…The results are unambiguous: there is a clear influence which can be experimentally derived and repeated. We will detail a few of our results here [33], demonstrating to the reader instantiated quantum informational effects of medically active compounds on cell growth and differentiation. Information associated with molecular influence upon biological systems can be substituted for the active compounds so as to mimic the effects of the source molecule as evidenced in experiments.…”
Section: The Alberto Foletti Research Teammentioning
confidence: 91%
See 1 more Smart Citation
“…The results of the present study agreed with others suggesting that signals could be transferred to target cells or aqueous systems by an oscillator (BRT instrument) when coupled to two electromagnetic coils, demonstrating the same biological activity, thus mimicking the biological function of the original chemical active molecule (Foletti et al, 2012). Earlier, Endler et al (1995) demonstrated that the metamorphosis of tadpoles could be greatly slowed down by transferring information from a toxic solution of the hormone thyroxin to the aquarium water, in a number or parallel blind trials.…”
supporting
confidence: 91%
“…Excitations are of great importance in the migration of energy and for the quantum computation of early life. The ElectroMagnetic Information Transfer Through Aqueous Systems (EMITTAS) procedure has demonstrated information flow within biological systems which eISSN 1303-5150 www.neuroquantology.com suggests that aqueous systems play a key role providing the basis for recording, storing, transferring and retrieving clinically effective quanta of information able to yield the selfregulation and self-regeneration potentiality of an organism both at local and systemic level (Foletti, 2015;Foletti et al, 2011).…”
Section: Quantum Biologics Led To the Origin Of Life And Consciousnesmentioning
confidence: 99%